Frequency of Coexistent Spinal Segment Variants: Retrospective Analysis in Asymptomatic Young Adults - Yoon, Edward S.; Pishgar, Farhad; Chhabra, Avneesh; Del Grande, Filippo; Carrino, John A. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Spinal segment variants are highly prevalent and can potentially lead to incorrect spinal enumeration and, consequently, interventions or surgeries at the wrong vertebral levels. Our aim was to assess the prevalence of spinal segment variants and to study the potential association among these variants in a population without histories of spine symptoms.MATERIALS AND METHODS: Consecutive computed tomography exams of 450 young adults originally evaluated for non-spinal conditions and without a history of spinal diseases from a single institution. In addition to using descriptive statistics for reporting frequencies of spinal segment variants, the association between these variants was studied by calculating odds ratios and their 95% confidence interval. Consecutive CT exams were evaluated to determine the total number of presacral segments, presence of cervical rib, thoracolumbar transitional vertebra, iliolumbar ligament, and lumbosacral transitional vertebra.RESULTS: The spinal segment distribution variants (an atypical number of presacral segments or an atypical distribution of thoracolumbar vertebrae), cervical rib, thoracolumbar transitional vertebra, and lumbosacral transitional vertebra were reported in 23.8%, 4.2%, 15.3%, and 26.4% of cases in our study population. The presence of a cervical rib or a thoracolumbar transitional vertebra was associated with concurrent lumbosacral transitional vertebra (OR = 3.28; 95% CI, 1.29–8.47 and 1.87; 95% CI, 1.08–3.20, respectively). The inability to visualize the iliolumbar ligament was also associated with the presence of cervical ribs (OR = 3.06; 95% CI, 1.18–7.80).CONCLUSIONS: In a population of asymptomatic young adults, spinal segment variants are both highly prevalent with a high rate of coexistence. When a spinal segment variant (eg, transitional vertebra) is diagnosed, additional imaging might be considered for accurate spine enumeration before interventions or operations.ILLiliolumbar ligamentLSTVlumbosacral transitional vertebraTLTVthoracolumbar transitional vertebra